Quality of Life Among HIV Positive Individuals in Kathmandu Valley and Eastern Region of Nepal - Agrawal, H; Mourya, R; Shrestha, RK; Agrawal, S (Kathmandu University Medical Journal, 2014)
Background The alarming increase of HIV/AIDS, inability to afford highly active anti-retroviral therapy, disability and stigma associated with the disease, loss of productivity due to illness, and chronic nature of the disease has made HIV/AIDS one of the most important public health problems in developing countries. The Quality of life assessment is focused on humanistic element and intervention resulting from this result may lead to better overall patient well being. Objective The aim of our study was to assess and compare the quality of life among HIV positive individuals in Kathmandu Valley & Eastern region. Methods The study was conducted among 228 HIV positive individuals from Eastern Nepal and 213 from Kathmandu valley and they were compared with an equal number of age-sex matched controls from the community. The instrument used was the WHO QOL-BREF Nepali questionnaire. Results The HIV positive individuals had significantly lower (P<0.001) QOL scores than the controls in the overall QOL and all the domains of life: Physical, Psychological, Social and Environmental. HIV positive individuals from Kathmandu valley scored significantly better (P<0.001) scores in the Physical and Environmental domains when compared to HIV positive individuals from Eastern region. HIV positive females had a significantly higher (P<0.02) QOL scores for overall QOL and overall perception of health than the males. Conclusion These findings suggest that HIV positive individuals have a poorer quality of life than the general population in Kathmandu valley & Eastern region of Nepal and interventions could be targeted to improve this aspect of their health. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10985 Kathmandu Univ Med J 2012;10(4):3-7.